Relationship between Sexual Satisfaction and Perceived Health Status among Married Older Adults - Din, Hazwan Mat; Minhat, Halimatus Sakdiah; Ibrahim, Rahimah; Akahbar, Siti Aisyah Nor (International Journal of Psychosocial Rehabilitation, 2020)
Study on impact of sexuality on perceived health status is lacking especially among older adults in Malaysia. This aim of this study was to examine the association between sexual satisfaction and perceived health status among married older adults in Malaysia. Data of this study was obtained through a cross-sectional study conducted at the end of 2014. A three-step hierarchical logistic regression using SPSS was conducted to assess the association between sexual satisfaction and perceived health. The findings from the analysis showed that sexual satisfaction in form of physical contact was significantly associated with perceived health status after controlling for sociodemographic variables, health variables and emotional sexual satisfaction. Further analysis showed that those having physical contact satisfaction had more than 12 times higher to have good perceived health status compared to those not having physical contact satisfaction (AOR = 11.14; 95% CI: 1.73, 71.87). The findings from this study highlighted the important of having satisfaction from sexual activity with partner to improve health in later life.